Education programmes for persons with type 1 diabetes using an insulin pump: A systematic review. Issue 5 (19th October 2020) - Rytter, Karen; Schmidt, Signe; Rasmussen, Lauge Neimann; Pedersen‐Bjergaard, Ulrik; Nørgaard, Kirsten
Abstract: Education is essential in insulin pump therapy, but literature in the field is limited. We systematically reviewed insulin pump education programmes and their effects in two situations as follows: (1) basic education at the start of insulin pump therapy, providing the study design enabled us to separate the effects of insulin pump therapy itself from the effects of education and (2) re‐education of experienced pump users. Population: individuals ≥16 years with type 1 diabetes using insulin pumps with or without continuous glucose monitoring. Systematic searches were run in MEDLINE, Embase, CINAHL and ERIC. Original studies reporting an effect of insulin pump education programmes were included if published in English between January 1999 and May 2019. Of 988 potentially relevant studies, 48 were assessed in full text. Nine studies fulfilled the inclusion criteria, including one randomised controlled trial. Educational approaches and settings were sparsely described in all studies, and the content was usually reported as teaching points. Two studies considered basic education, reporting evaluations of knowledge and application skills, and programme satisfaction. The remaining seven studies referred to re‐education. Two studies measured severe hypoglycaemic events before and after a re‐education intervention, both reporting a significant event reduction. HbA1c decreased significantly in three of four studies. Two studies reported increased knowledge and improved application skills. In conclusion, this review indicates benefits from basic education and from re‐education. The strength of the conclusions is limited by the low number of studies and study designs. High‐quality studies are needed comparing different approaches for insulin pump education.